Transcriptome and Expression Profiling Analysis of Recalcitrant Tea (Camellia sinensis L.) Seeds Sensitive to Dehydration - Xiaofang Jin; Dandan Liu; Linlong Ma; Ziming Gong; Dan Cao; Yanli Liu; Yeyun Li; Changjun Jiang (International Journal of Genomics)
The tea plant (Camellia sinensis (L.) O. Kuntze) is an economically important woody perennial nonalcoholic health beverage crop. Tea seeds are categorized as recalcitrant and are sensitive to dehydration treatment. However, the molecular basis of this phenomenon has not been investigated. Thus, we analyzed the genome-wide expression profiles of three dehydration stages using RNA-Seq and digital gene expression (DGE) technologies. We performed de novo assembly and obtained a total of 91,925 nonredundant unigenes, of which 58,472 were extensively annotated. By a hierarchical clustering of differentially expressed genes (DEGs), we found that 8929 DEGs were downregulated and 5875 DEGs were upregulated during dehydration treatment. A series of genes related to ABA biosynthesis and signal transduction, transcription factor, antioxidant enzyme, LEA protein, and proline metabolism that have been reported to function in dehydration process were found to be downregulated. Additionally, the expression profiles of 12 selected genes related to tea seed dehydration treatment were confirmed by qRT-PCR analysis. To our knowledge, this is the first genome-wide study elucidating the possible molecular mechanisms of sensitivity of recalcitrant tea seeds to dehydration. The results obtained in this study contribute to the preservation of tea seeds as genetic resources and can also be used to explore the mechanism of dehydration sensitivity of other recalcitrant seeds.